(untitled) (University Heart Journal, 2026)
Background: Osteoarthritis (OA) is a prevalent degenerative joint disorder increasingly associated with systemic comorbidities, particularly cardiovascular disease. Vitamin D deficiency is common in OA patients and may contribute to adverse cardiovascular outcomes through metabolic and inflammatory mechanisms. Aim of the study: To evaluate the association between serum vitamin D levels and cardiovascular risk in patients with osteoarthritis. Methods: This cross-sectional study included 110 patients with clinically and radiologically confirmed OA. Serum 25(OH)D levels were categorized as deficient (<20 ng/mL) or sufficient (≥20 ng/mL). Cardiovascular risk was assessed using lipid profile, blood pressure, and fasting blood glucose. OA severity was graded using the Kellgren–Lawrence system. Statistical analysis was performed using SPSS version 26.0, with p<0.05 considered significant. Result: Vitamin D deficiency was found in 48.18% of participants. Deficient patients had significantly higher total cholesterol (224.6 ± 36.5 vs 197.8 ± 34.2 mg/dL, p<0.001), LDL (145.3 ± 30.7 vs 120.5 ± 28.9 mg/dL, p<0.001), triglycerides (192.1 ± 42.8 vs 162.3 ± 40.5 mg/dL, p=0.001), and systolic BP (144.2 ± 17.6 vs 133.5 ± 18.1 mmHg, p=0.003), along with lower HDL levels (38.6 ± 7.9 vs 43.8 ± 8.2 mg/dL, p=0.002). High cardiovascular risk was more prevalent among deficient patients (49.06% vs 26.32%, p=0.01). Severe OA was also significantly associated with vitamin D deficiency (69.81% vs 47.37%, p=0.02). Multivariable analysis showed vitamin D deficiency independently predicted high cardiovascular risk (AOR 2.9, 95% CI 1.4–6.1, p=0.004). Conclusion: Vitamin D deficiency is significantly associated with increased cardiovascular risk and greater disease severity in osteoarthritis patients, highlighting the importance of integrated clinical evaluation and management. University Heart Journal 2026; 22(1): 21-27